A Finite Element Study on the Structural Behavior of a Dual-Axis Solar Tracking System - Rahal, Rayan; Matta, Mark; Rishmany, Jihad (Kurdistan Journal of Applied Research, 2026)
Solar panels have become a highly effective and widely adopted source of renewable energy. Extensive research has been devoted to improving the materials used in photovoltaic systems to enhance efficiency, durability, and performance. Continuous efforts have also focused on strategies to maximize solar energy capture; from materials used to determining the optimal angle and direction for panel installation for optimal energy capture. Within this context, this study presents the design and structural analysis of an innovative dual-axis solar tracker, developed and simulated using SolidWorks. The design consists of three main components: the main structure, which can hold up to a total of 18 panels arranged in a 3x6 matrix; the rotating structure, to which the main structure is attached via two flanged bearings at the ends to provide tilt motion; and the stationary base, to which the rotating structure is connected via a slew bearing that enables rotation in the east-west direction. The overall design accounts for a total system weight of approximately 4000 kg. To ensure safe operation, Finite Element Analysis is conducted under extreme-case wind loading conditions to assess structural integrity. Key results included a maximum von Mises stress of 196.6 MPa, a maximum deflection of 37.81 mm, and a minimum factor of safety of 1.122. Convergence is successfully achieved for all components, with relative errors below 1%, confirming the reliability and accuracy of the simulation outcomes.